"Compassionate" Cases of the Jarvik 2015 Ventricular Assist Device. Issue 9 (11th January 2021) - Spinner, Joseph A.; Tunuguntla, Hari P.; Tume, Sebastian C.; Elias, Barbara A.; Mcmullen, Jason; John, Rija; Choudhry, Swati; Price, Jack F.; Denfield, Susan W.; Dreyer, William J.; Adachi, Iki
Abstract : Supplemental Digital Content is available in the text. Abstract : The Jarvik 2015 Ventricular Assist Device (VAD) (Jarvik Inc, New York, NY) is the first and currently only continuous-flow VAD specifically designed for small children, and it is being evaluated in the so-called Pump for Kids, Infants, and Neonates (PumpKIN) trial. Due to the strict inclusion criteria of the trial, there have been a group of patients who failed to meet the criteria and therefore received the Jarvik 2015 VAD under the designation of "compassionate use." This is the same phenomenon seen previously during the Berlin Heart EXCOR trial. While we await the results of the PumpKIN trial, which will report the device performance in a strictly selected population, the compassionate use cases represent actual "real world" experiences. We describe herein our experience of two compassionate use cases. In particular, this report has a special emphasis on the power consumption and hemolysis and inflammatory lab profile of the Jarvik 2015 VAD as hemocompatibility was the primary focus of the developmental and the preclinical phases.